Familial acute aortic dissection associated with a novel ACTA2 germline variant - Strecker, Thomas; Wiesmueller, Felix; Rudnik-Schoeneborn, Sabine; Hoyer, Juliane; Wiesmann da Silva Reis, André; Weyand, Michael; Agaimy, Abbas (Virchows Archiv, 2022)
Aortic dissection is a life-threatening cardiovascular disease. Hereditary disorders are responsible for a small percentage of cases. Nonetheless, it is important to identify genetic causes, as they are often autosomal dominantly inherited and are of life-saving importance if we can identify persons at risk. Mutations of the ACTA2 gene are the most common cause of non-syndromic familial aortic disease. Exploration of the genetic background in suspected familial cases and determination of the exact etiology are mandatory for management and establishing appropriate follow-up strategies due to the risk of fatal recurrences. Herein, we present a 21-year-old male with a familial acute aortic dissection associated with novel ACTA2 germline variant and discuss the management and surveillance considerations.
CRIS-Team WoS Importer:2022-08-05